Nutritional Geometric Profiles of Insulin/IGF Expression in Drosophila melanogaster. - Stephanie Post; Marc Tatar (PLoS ONE, 2016)
Insulin/IGF signaling (IIS) in Drosophila melanogaster is propagated by eight Drosophila insulin-like peptides (dilps) and is regulated by nutrition. To understand how dietary protein and sugar affect dilp expression, we followed the analytical concepts of the Nutritional Geometric Framework, feeding Drosophila adults media comprised of seven protein-to-carbohydrate ratios at four caloric concentrations. Transcript levels of all dilps and three IIS-regulated genes were measured. Each dilp presented a unique pattern upon a bivariate plot of sugar and protein. Dilp2 expression was greatest upon diets with low protein-to-carbohydrate ratio regardless of total caloric value. Dilp5 expression was highly expressed at approximately a 1:2 protein-to-carbohydrate ratio and its level increased with diet caloric content. Regression analysis revealed that protein-to-carbohydrate ratio and the interaction between this ratio and caloric content significantly affects dilp expression. The IIS-regulated transcripts 4eBP and InR showed strikingly different responses to diet composition: 4eBP was minimally expressed except when elevated at low caloric diets. InR expression increased with protein level, independent of caloric content. Values of published life history traits measured on similar diets revealed correlations between egg production and the expression of dilp8 4eBP, while low protein-to-carbohydrate ratio diets associated with long lifespan correlated with elevated dilp2. Analyzing how nutient composition associates with dilp expression and IIS reveals that nutritional status is modulated by different combinations of insulin-like peptides, and these features variously correlate to IIS-regulated life history traits.